Document management and environmental sustainability: guidelines for an archival policy in the UFCG General Archive (Seminário Internacional de Informação, Tecnologia e Inovação, 2025)
Document management is essential to ensure access to information, the preservation of institutional memory, and administrative efficiency. This study investigated document management practices in the general archive of the Federal University of Campina Grande, focusing on environmental sustainability, with the goal of proposing guidelines for an institutional archival policy. This qualitative, exploratory-descriptive study employed questionnaires administered to staff involved in document production and management. The results indicate specific and non-standardized practices, fragility in the use of archival instruments, and a lack of institutional sustainability guidelines. The conclusion is that a sustainable archival policy capable of articulating governance, training, and socio-environmental responsibility is urgently needed.
Keywords: document management; archival sustainability; public policies